8(x-1)+2(x-1)=90

Simple and best practice solution for 8(x-1)+2(x-1)=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(x-1)+2(x-1)=90 equation:


8(x-1)+2(x-1)=90

We simplify the equation to the form, which is simple to understand
8(x-1)+2(x-1)=90

Reorder the terms in parentheses
+(+8x-8)+2*(x-1)=90

Remove unnecessary parentheses
+8x-8+2+*(+x-1+)=+90

Reorder the terms in parentheses
+8x-8+(+2x-2)=90

Remove unnecessary parentheses
+8x-8+2x-2=+90

We move all terms containing x to the left and all other terms to the right.
+8x+2x=+90+8+2

We simplify left and right side of the equation.
+10x=+100

We divide both sides of the equation by 10 to get x.
x=10

See similar equations:

| -50+x+x+x=-11 | | ab=3x+12 | | 4c-5c+8.4=3.6-2c-4.2 | | 63=3v | | 87+x=120 | | -45+x=-31 | | 4+6x=7+2x | | -2(-3x+2)=-6 | | 3(2b-4)=5(b+2) | | 105x^2-182x+56=0 | | 7a+8=8a-2 | | 3(4x+7)+9(x-1)=180 | | 3x-5-4x=6-2x | | s+1.2=-.2 | | 107-2x=25x+23 | | 3x-2=3(x-0.6666666666666666) | | x^4+12x^2-27=0 | | 63y-42=64y | | 7x-1+22(x-1)=180 | | 6(x-4)+9=2x+4(-3+x) | | 3x^3-8x^2+4x=0 | | 5x+3y+12x-7xy= | | 16=1d+6 | | 4x+8+2x=5x-1 | | -4x^2-6x+4=0 | | 5x+3+6x-1=90 | | 4p-3q+7p-2q= | | -6(3-3)-8(6x+5)=32 | | 20x-27x-8=0 | | 3(cq-5)=2(q+5) | | 2x+5x+42=0 | | 9x+9=7x+39 |

Equations solver categories